Pengguna Media Interaktif Sebagai Kenyataan Maya: Studi Resepsi Khalayak Suarasurabaya.net Sebagai Media Interaktif - Ido Prijana Hadi (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
My aim in writing this paper is to describe that in this fast-changing world, media in Indonesia has undergone a rapid transformation. Digital technology continues to reshape the mass media landscape using internet technology. Internet brings a technical communication revolution, a fundamental change takes place in the structure of connections, artificial memories and the reproduction of their content. Internet technology has made communication much easier and less expensive. It has attracted many people and has penetrated into people’s daily lives. The mass media also have accepted the internet. Almost all forms of traditional media (old media) in local media, such as radio, television, and newspaper have extended their work into this new field. The internet and the World Wide Web have both significantly influenced modern journalism. In online media allows readers to enjoy browsing their product and service of contents, such as news feed, podcasts, desktop alert, news on mobile phones, PDA and others mobile devices. Online media offer not only text but also digital images , audio file, moving images (video), internet radio and internet t v. The interactive features of the internet seemingly imply that online media have more advantages than traditional media forms (old media). So, the internet have dramatically evolved become new media with characteristic multimedia, hypertext, interactivity, archives , and virtuality. The most important structural new media characteristic is the integration of telecommunications, data communications and mass communication in a single medium – it is the convergence. It should be pointed out that the trend toward digital is affecting the various media and brings the local media in East Java to become a global media, where breaking news from Surabaya or anywhere in East Java is transmitted to around the world in a matter of minutes . The research was carried out to find out how user reception on convergence media, journalism and local media on the site of SuaraSurabaya.net and how to access subjective meanings that they have created based on t heir understanding on online media so far. The research is also interested in looking into user reception on information and communication technology based on its relevance with the selected theme namely discourses on global media in website of Radio Suara Surabaya.